Contempt of Court: Suatu Perbandingan antara Berbagai Sistem Hukum - Ida Keumala Jeumpa (Kanun Jurnal Ilmu Hukum, 2014)
This paper is based on the justice developments nowadays. One of them is many decisions of judges are not enforced. A court is the fort of justice is disrespectful. Even, the society considers that the justice process is not fair. The phenomenon is over shown. The presses, by its opinions have contributed on undermining the court and make it disrespectful. Such actions in the English law are known as contempt of court and it is not found such regulation in the Indonesian penal code. Contempt of Court: A Comparison Among Vary Legal Systems